Coronary Artery Fistula Presenting as Unstable Angina Pectoris in Patients with Antiphospholipid Syndrome - Şerafettin Demir; Ceyhun Yucel; Mucahit Tufenk; Aydin Rodi Tosu; Murat Selcuk; Abdi Bozkurt (Case Reports in Medicine)
The cardiovascular system is one of the primary targets in patients with antiphospholipid syndrome. The valves are the most frequently affected. Atherosclerosis and coronary thrombosis are also seen. The risk of acute coronary syndrome is 10 times higher in patients with APS. We present an APS patient case who was hospitalized with acute coronary syndrome and who was later found to have coronary artery fistula.